Family and Person: A One-on-One and Constitutive Relationship - Melendo Granados, Tomás (Metafísica y Persona, 2017)
There is no family without the person, but neither is there a person without the family. The radical origin of the family lies in the excess of being proper to any person; that of the human family, and inasmuch as it is human, is reinforced by the needful characteristic of all males and females, who need each other in order to attain personal fulfillment. In all families, strictly personal relationships are established, which are directed by the unconditional reciprocal love, or rather, unconditional and un-condition-able love.